Optimised radar processors (Peter Peregrinus Ltd. on behalf of the Institution of Electrical Engineers, 1987)
Annotation The first volume in a new series. Contributed papers give a theory of radar signal processing at a level accessible and useful to practicing radar engineers concerned with design and analysis. No index. Annotation(c) 2003 Book News, Inc., Portland, OR (booknews.com).
Keywords: Radar.; Signal processing.; elektronické knihy; electronic books